Precipitation as a driver of phytoplankton ecology in coastal waters: A climatic perspective. (5th September 2015) - Thompson, Peter A.; O'Brien, Todd D.; Paerl, Hans W.; Peierls, Benjamin L.; Harrison, Paul J.; Robb, Malcolm
Abstract: Climatic change is shaping our planet's ecosystems yet our capacity to predict the consequences and prepare for the future remains rudimentary. Changes to the hydrological cycle mean that large regions of the planet are experiencing changes in precipitation. Responses by phytoplankton were assessed in three regions: 1) globally, 2) in regions that are wet and getting wetter, 3) in regions that are dry and getting drier. Using long-term time-series data the temporal variation in precipitation was compared with variation in chlorophyll a, diatoms, dinoflagellates, chlorophytes, chrysophytes and euglenophytes from 106 sites worldwide. The results demonstrate that phytoplankton responses to precipitation depend upon the season and region. In general phytoplankton responded more positively to increased precipitation during summer rather than winter. Increased precipitation during winter was likely to reduce chlorophyll a, diatoms and chrysophytes, whereas increasing precipitation in summer was likely to increase chlorophyll a and favor chlorophytes. Within regions that are wet and getting wetter chlorophyll a increased and dinoflagellate abundances were reduced in wet autumns; while diatom abundances were reduced in wet springs. In dry and drying ecosystems the abundances of chlorophytes decreased during dry springs and summers. The existence of these widespread patterns of phytoplankton abundance associated with inter annual variability in precipitation improves our capacity to predict the future composition of phytoplankton communities in estuarine and coastal water bodies. Highlights: Phytoplankton community composition showed changes associated with climate variability. Changes in seasonal precipitation were quantitatively linked with responses by particular Phyla. Decreasing precipitation was associated with fewer chlorophytes. Increasing precipitation affected spring diatom blooms and truncated autumn dinoflagellate blooms. The timing and magnitude of precipitation influenced phytoplankton community composition in a consistent manner.